Hepatic fat assessment using advanced Magnetic Resonance Imaging - Pang, Yong; Yu, Baiying; Zhang, Xiaoliang (Quantitative Imaging in Medicine and Surgery; Vol 2, No 3 (September 27, 2012): Quantitative Imaging in Medicine and Surgery, 2012)
Magnetic Resonance Imaging is capable of providing clinically-valuable images for hepatic diseases such as the fatty liver and has become a promising noninvasive method in evaluating human liver under normal and diseased conditions (1-9). Fatty liver is one of the most common abnormalities. Recent surveys have shown that it affects up to 15% of the general population and it is higher among those with obesity and high alcohol consumption (10-12).